1992
DOI: 10.1073/pnas.89.13.5892
|View full text |Cite
|
Sign up to set email alerts
|

Fumarase C, the stable fumarase of Escherichia coli, is controlled by the soxRS regulon.

Abstract: Fumarase C was strongly induced by paraquat in a parental strain of Escherichia coli but was not induced in a strain lacking the soxRS response. Moreover, a strain that constitutively expresses the soxRS regulon contained more fumarase C than did the parental strain. The Mn-containing superoxide dismutase and glucose-6-phosphate dehydrogenase, members of the soxRS regulon, were similarly induced by paraquat. Mutational defects in glucose-6-phosphate dehydrogenase increased the induction of fumarase C by paraqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
173
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(185 citation statements)
references
References 43 publications
11
173
1
Order By: Relevance
“…Recently, we demonstrated that protein can be reversibly inactivated in vitro by reduction of its Fe-S centers with dithionite under conditions that should not have resulted in dissociation of the Fe-S centers (3). This finding was consistent with an observation that the regulon's induction may be sensitive to the redox balance of the cell (11). However, what we can demonstrate in vitro is not necessarily related to what happens in vivo.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Recently, we demonstrated that protein can be reversibly inactivated in vitro by reduction of its Fe-S centers with dithionite under conditions that should not have resulted in dissociation of the Fe-S centers (3). This finding was consistent with an observation that the regulon's induction may be sensitive to the redox balance of the cell (11). However, what we can demonstrate in vitro is not necessarily related to what happens in vivo.…”
supporting
confidence: 93%
“…The model also postulated that there must be an efficient redox pathway for maintaining the autooxidizable protein in a reduced form during aerobic growth (11,30). The present work demonstrates that pathway.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Thus, unlike gnd, zwf expression is transcriptionally activated by SoxS during episodes of oxidative stress induced by exposure of E. coli to superoxide-generating agents such as paraquat (17,18,39). Indeed, E. coli strains deleted for zwf are hypersensitive to oxidative stress, thus making zwf a pivotal member of the soxRS regulon (18,21). In addition, treatment of cells with several antibiotics and aromatic weak acids appears to activate zwf transcription through the action of marA, thus making zwf a member of the multiple antibiotic resistance (mar) regulon (2,6,7,14,16).…”
mentioning
confidence: 99%